2023
DOI: 10.1021/acs.jmedchem.3c00173
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Linvencorvir (RG7907), a Hepatitis B Virus Core Protein Allosteric Modulator, for the Treatment of Chronic HBV Infection

Abstract: Described herein is the first-time disclosure of Linvencorvir (RG7907), a clinical compound and a hepatitis B virus (HBV) core protein allosteric modulator, for the treatment of chronic HBV infection. Built upon the core structure of hetero aryl dihydropyrimidine, RG7907 was rationally designed by combining all the drug-like features of low CYP3A4 induction, potent anti-HBV activity, high metabolic stability, low hERG liability, and favorable animal pharmacokinetic (PK) profiles. In particular, the chemistry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
(65 reference statements)
0
19
0
Order By: Relevance
“…MS: calcd 371 (MH + ), measured 371 (MH + ). 1 3-(4-Fluorophenyl)-N-(m-tolyl)-6,7-dihydro-4H-pyrazolo[1,5-a]pyrazine-5-carboxamide (14). Yield: 33%.…”
Section: N-benzyl-3-(4-fluorophenyl)-67-dihydro-4h-pyrazolo[15-a]pyra...mentioning
confidence: 99%
See 1 more Smart Citation
“…MS: calcd 371 (MH + ), measured 371 (MH + ). 1 3-(4-Fluorophenyl)-N-(m-tolyl)-6,7-dihydro-4H-pyrazolo[1,5-a]pyrazine-5-carboxamide (14). Yield: 33%.…”
Section: N-benzyl-3-(4-fluorophenyl)-67-dihydro-4h-pyrazolo[15-a]pyra...mentioning
confidence: 99%
“…Two types of distinct CpAMs (Figure ) have been advanced into clinical development. The type I CpAM is the heteroaryldihydropyrimidine (HAP) series of compounds, such as BAY 41-4109 and RG7907 (Linvencovir), which accelerate and misdirect the assembly of HBV core proteins to induce the formation of abnormal nucleocapsids, presumably followed by the protein degradation by host proteases . The type II CpAM is exemplified by NVR-3-778, JNJ-379, and ABI-H0731, which accelerates the assembly of core proteins to form empty capsids without the incorporation of pregenomic RNA (pgRNA).…”
Section: Introductionmentioning
confidence: 99%
“…hydroxyl, methoxy, vinyl, ethynyl, cyano, and aldehyde (6a- (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)). The results indicated that these substitutions did not enhance the anti-HBV activity, suggesting that they were not effective at the protein-solvent interface.…”
Section: Rsc Medicinal Chemistry Research Articlementioning
confidence: 99%
“…Since the late 1990s, various chemotypes of compounds have been discovered to promote the assembly of Cp into aberrant or empty capsids, effectively inhibiting HBV replication. Examples of these compounds include heteroaryldihydropyrimidines (HAPs), [16][17][18][19][20] sulfamoylbenzamides (SBAs), 21 phenylpropenamides (PPAs), 22 and dibenzothiazepines (DBTs) 23 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation